Family control, institutional environment and cash dividend policy: Evidence from China - Zhihua Wei; Shinong Wu; Changqing Li; Wei Chen (China Journal of Accounting Research, 2011)
Using a sample of 1486 Chinese A-share listed companies for the period 2004–2008, this study empirically tests the impact of family control, institutional environment and their interaction on the cash dividend policy of listed companies. Our results indicate that (1) family firms have a lower cash dividend payout ratio and propensity to pay dividends than non-family firms; (2) a favorable regional institutional environment has a significant positive impact on the cash dividend payout ratio and propensity to pay dividends of listed companies; and (3) the impact of the regional institutional environment on cash dividends is stronger in family firms than in non-family firms. Somewhat surprisingly, we find that controlling family shareholders in China may intensify Agency Problem I (the owner–manager conflict) rather than Agency Problem II (the controlling shareholder–minority shareholder conflict), and thus have a significant negative impact on cash dividend policy. In contrast, a favorable regional institutional environment plays a positive corporate governance role in mitigating Agency Problem I and encouraging family firms to pay cash dividends.